2012
DOI: 10.1159/000334928
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Recruitment and Activation of T Cells in Diabetic Nephropathy

Abstract: Background/Aims: Recent evidence has shown that an inflammatory process is involved in the development and progression of diabetic nephropathy. This study examined the impact of activated intrarenal lymphocytes in this inflammatory process. Methods: We studied T cell recruitment in mice with streptozotocin (STZ)-induced diabetes by flow cytometry and immunohistochemistry. The kidney biopsy specimens from patients with type 2 diabetes mellitus and diabetic nephropathy were evaluated by immunohistochemistry. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
125
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(126 citation statements)
references
References 60 publications
1
125
0
Order By: Relevance
“…This indicates that IL-7 can contribute to the pathogenesis of autoimmune diabetes by enabling effector/memory T cells to remain in a functionally competent state. In a recent study, an aberrant recruitment and activation of effector T cells in T2D-associated nephropathy was demonstrated, and found to be correlated with the amount of proteinuria [42]. As such, the increased IL-5 and IL-7 levels detected in the prediabetic African American females in our study might indicate that they are at increased risk to develop diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 58%
“…This indicates that IL-7 can contribute to the pathogenesis of autoimmune diabetes by enabling effector/memory T cells to remain in a functionally competent state. In a recent study, an aberrant recruitment and activation of effector T cells in T2D-associated nephropathy was demonstrated, and found to be correlated with the amount of proteinuria [42]. As such, the increased IL-5 and IL-7 levels detected in the prediabetic African American females in our study might indicate that they are at increased risk to develop diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 58%
“…The first contribution of the studies was about the increase in local accumulating T cells in diabetic experimental models. Xiao et al [10] and Moon et al [11] showed an increase in CD4 and CD8 lymphocytes in diabetic mouse, these changes were observed in glomeruli and interstice.…”
Section: T Lymphocytesmentioning
confidence: 92%
“…Bending and colleagues observed in the renal parenchyma that the absolute number and percent of activated T-lymphocytes in the renal parenchyma was significantly higher in insulin dependent patients with diabetes with proteinuria than without proteinuria [16,31]. CD3+ T cells have also been found in the interstitium of mice with streptozotocin induced diabetes and proteinuria [32].T cells infiltrating the diabetic kidney produce inflammatory cytokines, such as TNF-α, interleukin-6 and interferon-γ. These T cells likely contribute to local inflammation and tissue damage [32,33].…”
Section: Role Of T Lymphocytes In Diabetic Nephropathymentioning
confidence: 99%
“…CD3+ T cells have also been found in the interstitium of mice with streptozotocin induced diabetes and proteinuria [32].T cells infiltrating the diabetic kidney produce inflammatory cytokines, such as TNF-α, interleukin-6 and interferon-γ. These T cells likely contribute to local inflammation and tissue damage [32,33]. Using db/db mice Eller et al have recently shown that suppressing the activity of T cells prevents development of diabetic nephropathy.…”
Section: Role Of T Lymphocytes In Diabetic Nephropathymentioning
confidence: 99%
See 1 more Smart Citation